2001
DOI: 10.1155/2001/852674
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Analysis of Comparative Genomic Hybridization (CGH) Data Using Self‐Organizing Maps: Application to Prostate Carcinomas

Abstract: Comparative genomic hybridization (CGH) is a modern genetic method which enables a genome‐wide survey of chromosomal imbalances. For each chromosome region, one obtains the information whether there is a loss or gain of genetic material, or whether there is no change at that region. Usually it is not possible to evaluate all 46 chromosomes of a metaphase, therefore several (up to 20 or more) metaphases are analyzed per individual, and expressed as average. Mostly one does not study one individual alone but gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…This observation is consistent with the published literature [for review, see Abate-Shen and Shen (2000)] that loss of one or more genes residing on 8p is most critical for prostate carcinogenesis. In addition, a recent cluster analysis of CGH data from stage T2N0 tumors by Mattfeldt et al (2001) found that, although losses on chromosome arms 6q, 8p, and 13q were frequent, only the loss of 8p has the largest prognostic importance based on clinical follow-up. An additional five steps in the model increased the percentage correct prediction of the stage of tumors to over 90%.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is consistent with the published literature [for review, see Abate-Shen and Shen (2000)] that loss of one or more genes residing on 8p is most critical for prostate carcinogenesis. In addition, a recent cluster analysis of CGH data from stage T2N0 tumors by Mattfeldt et al (2001) found that, although losses on chromosome arms 6q, 8p, and 13q were frequent, only the loss of 8p has the largest prognostic importance based on clinical follow-up. An additional five steps in the model increased the percentage correct prediction of the stage of tumors to over 90%.…”
Section: Discussionmentioning
confidence: 99%
“…it can be considered as the supervised counterpart to self-organising maps (SGMs) (KOHONEN, 1997;MATTFELDT et al, 2001b;2002;2004a). When we have decided on a set of k variables to evaluate, the data of a single case can be represented as a vector or point in the corresponding k-dimensional input space.…”
Section: Learning Vector Quantisation (Lvq)mentioning
confidence: 99%
“…For the present study the source files were compiled and used under Linux [10,11]. The result consists of tables where each case is assigned to one cluster.…”
Section: Somsmentioning
confidence: 99%
“…The classical implementation of a SOM is the package SOM_PAK [8,9], which can be obtained as free academic software from the internet at: http://www.cis.hut.fi/research/ som-research/nnrc-programs.shtml. For the present study the source files were compiled and used under Linux [10,11]. The result consists of tables where each case is assigned to one cluster.…”
Section: Somsmentioning
confidence: 99%
See 1 more Smart Citation